(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the creative work of the renowned statesman Sharof Rashidov. Specifically, the article analyzes the multifaceted creative work of the writer and statesman based on various historical sources.